Low water loss hydrogel and its preparation method and application
By adjusting the ratio of water and moisturizer in the hydrogel, and combining specific additives and structural design, the problem of high water loss rate of hydrogel is solved, low water loss rate and high water holding capacity are achieved, and product life and User experience.
Patent Information
- Application Number
- CN202110481415.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-04-30
AI Technical Summary
The current hydrogel has a high water loss rate, which affects its service life and massage experience. If the proportion of moisturizer is too low or too high, it will lead to excessive water loss or poor conductivity.
By limiting the weight ratio of water and humectant in the hydrogel to the range of 0.4-0.6, combining crosslinking agents, photoinitiators, water-soluble chloride salts, polymeric monomers, and acrylate monomers, a combination of a crosslinking agent, a photoinitiator, a water-soluble chloride salt, a polymeric monomer, and an acrylate monomer, a Low water loss hydrogel, designed with a two-layer structure to improve adhesion and avoid excessive adhesion.
The water loss rate of hydrogel is significantly reduced to less than 9%, improving water holding capacity and product life cycle, while ensuring conductive performance and user experience.
Smart Images

Figure HDA0003049410350000011 
Figure HDA0003049410350000021 
Figure HDA0003049410350000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional hydrogels, and in particular relates to a low water loss hydrogel and a preparation method and application thereof. Background Art
[0002] As the pace of life continues to accelerate, more and more sub-health problems have emerged. In order to cope with this problem and relieve the fatigue caused by the fast-paced life, massage equipment has been widely used. The massage equipment can eliminate the pain caused by fatigue or rheumatism. By stimulating the meridians and nerves of the human body, it can coordinate and balance the functions of the internal organs of the human body and promote the body's fluid circulation. The metal electrode of the massage equipment is in contact with the skin. Because there are many uneven places in the microstructure of the skin, when the low-frequency current acts on the uneven places, it will cause discomfort and tingling. Hydrogel, as an auxiliary material, is interspersed between the metal electrode and the skin, playing a good buffering role. Because the gel has the characteristics of softness and conductivity, it can cover the defects on the skin surface while bonding the skin, so that the electrode current acts evenly on the skin, and at the same time it can significantly increase the strength of the action. Summary of the invention
[0003] The inventors found that the water content in the hydrogel affects the service life of the hydrogel. If the water is lost too much, the use effect of the hydrogel will be affected, resulting in a poor massage experience. The water loss rate of existing hydrogels is above 16%, which is relatively high. How to improve the water holding capacity of the hydrogel has become an urgent problem to be solved.
[0004] In view of this, the purpose of the present invention is to propose a low water loss hydrogel and its preparation method and application. By limiting the weight ratio of water and humectant in the hydrogel to (0.4-0.6):1, the water loss rate of the hydrogel is greatly reduced. The water loss rate of the hydrogel in the embodiment of the present invention is less than 9%, thereby improving the water holding capacity of the hydrogel, thereby greatly improving the life cycle of the hydrogel product. The inventors found that if the proportion of humectant is too low, the hydrogel will lose water too quickly and have poor water retention; if the proportion of humectant is too high, the conductive properties of the hydrogel will deteriorate, and the humectant will precipitate, thereby affecting the product experience.
[0005] In one aspect of the present invention, the present invention provides a low water loss hydrogel. According to an embodiment of the present invention, the low water loss hydrogel comprises: water, a humectant, a cross-linking agent, a photoinitiator, a water-soluble chloride salt, a polymerization monomer and an acrylate monomer;
[0006] The weight ratio of the water to the moisturizing agent is (0.4-0.6):1.
[0007] According to the low water loss hydrogel of the embodiment of the present invention, by limiting the weight ratio of water and humectant in the hydrogel to (0.4-0.6):1, the water loss rate of the hydrogel is greatly reduced, and the water loss rate of the hydrogel is less than 9%, thereby greatly improving the life cycle of the hydrogel product. The inventors found that if the proportion of the humectant is too low, the hydrogel will lose water too quickly and have poor water retention; if the proportion of the humectant is too high, the conductive properties of the hydrogel will deteriorate, and the humectant will precipitate.
[0008] In addition, the low water loss hydrogel according to the above embodiment of the present invention may also have the following additional technical features:
[0009] In some embodiments of the present invention, the composition comprises: 2-4.5 parts by weight of water, 3.1-7.5 parts by weight of a moisturizer, 0.001-0.14 parts by weight of a crosslinker, 0.001-0.12 parts by weight of a photoinitiator, 0.02-0.3 parts by weight of a water-soluble chloride salt, 1-5 parts by weight of a polymerizable monomer, and 0.1-2 parts by weight of an acrylate monomer.
[0010] In some embodiments of the present invention, the water is selected from at least one of ultrapure water, distilled water and deionized water.
[0011] In some embodiments of the present invention, the humectant is selected from at least one of glycerin, methylpropanediol, 1,3-propylene glycol and 1,2-hexanediol.
[0012] In some embodiments of the present invention, the cross-linking agent is selected from at least one of aliphatic amine cross-linking agents, aromatic amine cross-linking agents, polyamide cross-linking agents and polyether amine cross-linking agents.
[0013] In some embodiments of the present invention, the aliphatic amine cross-linking agent is selected from at least one of MBA, DETA, DACH and 4,4'-PACM.
[0014] In some embodiments of the present invention, the photoinitiator has a model number selected from at least one of 2959, 1173, 907 and 184.
[0015] In some embodiments of the present invention, the water-soluble chloride salt is selected from at least one of anhydrous lithium chloride, sodium chloride and ammonium chloride.
[0016] In some embodiments of the present invention, the polymerizable monomer is selected from at least one of acrylamide monomer, acrylic acid monomer, sodium acrylate monomer and chitosan monomer.
[0017] In some embodiments of the present invention, the acrylic acid ester monomer is selected from at least one of hydroxyethyl methacrylate and hydroxypropyl methacrylate.
[0018] In some embodiments of the present invention, the low water loss hydrogel further comprises a fragrance additive.
[0019] In some embodiments of the present invention, the flavor additive is selected from at least one of essence and essential oil.
[0020] In some embodiments of the present invention, the low water loss hydrogel further comprises a cooling agent.
[0021] In some embodiments of the present invention, the cooling agent is selected from at least one of mint flavor, menthol and menthol.
[0022] In some embodiments of the present invention, the low water loss hydrogel further comprises 0.0015 parts by weight of a skin conditioning agent.
[0023] In some embodiments of the present invention, the skin conditioning agent is selected from at least one of rose water and p-hydroxyacetophenone.
[0024] In some embodiments of the present invention, the low water loss hydrogel includes a first layer of colloid and a second layer of colloid, the second layer of colloid is used to adhere to one side of the electrode of the massage device; the weight ratio of the crosslinker in the first layer of colloid to the crosslinker in the second layer of colloid is (2.5-1.5):1. Therefore, by setting a two-layer structure, the content of the crosslinker in the second layer of colloid that adheres to one side of the electrode of the massage device is lower, so that the adhesion of the second layer of colloid is stronger, which is conducive to adhesion to the electrode of the massage device, while avoiding the situation that the adhesion of the first layer of colloid that contacts the skin is too strong, and it is easy to adhere to the skin and difficult to detach from the skin.
[0025] In some embodiments of the present invention, the thickness of the first colloid layer is 0.6-0.8 mm, and the thickness of the second colloid layer is 0.2-0.4 mm.
[0026] In another aspect of the present invention, the present invention provides a method for preparing the above-mentioned low water loss hydrogel. According to an embodiment of the present invention, the method comprises:
[0027] (1) mixing water, a humectant, a crosslinking agent, a photoinitiator and a water-soluble chloride salt, and stirring to form a first mixed solution;
[0028] (2) mixing the polymerizable monomer with the first mixed solution and stirring to form a second mixed solution;
[0029] (3) mixing the acrylic acid ester monomer with the second mixed solution and stirring to form a third mixed solution;
[0030] (4) The third mixed solution is transferred to a release film and UV-cured to obtain a low water-loss hydrogel.
[0031] According to the method of using the low water loss hydrogel according to an embodiment of the present invention, the method greatly reduces the water loss rate of the hydrogel by limiting the weight ratio of water and moisturizer in the hydrogel to the range of (0.4-0.6):1, and the water loss rate of the hydrogel is less than 9%, thereby improving the water holding capacity of the hydrogel, thereby greatly improving the life cycle of the hydrogel product. The inventors found that if the proportion of moisturizer is too low, the hydrogel will lose water too quickly and have poor water retention; if the proportion of moisturizer is too high, the conductive properties of the hydrogel will deteriorate, and the moisturizer will precipitate, thereby affecting the product experience.
[0032] In addition, the method for preparing the low water loss hydrogel according to the above embodiment of the present invention may also have the following additional technical features:
[0033] In some embodiments of the present invention, step (1) comprises the following steps:
[0034] (1-1) mixing the water and the moisturizing agent and stirring to form a fourth mixed solution;
[0035] (1-2) mixing the cross-linking agent with the fourth mixed solution and stirring to form a fifth mixed solution;
[0036] (1-3) mixing the photoinitiator with the fifth mixed solution and stirring to form a sixth mixed solution;
[0037] (1-4) The water-soluble chloride salt is mixed with the sixth mixed solution and stirred to obtain a first mixed solution.
[0038] In some embodiments of the present invention, in step (1-1), the stirring speed is 100-500 rpm, and the stirring time is 5-10 min.
[0039] In some embodiments of the present invention, in steps (1-2), (1-3) and (1-4), the stirring speed is independently 200-600 rpm, and the stirring time is independently 5-10 min.
[0040] In some embodiments of the present invention, step (1) is performed by heating and stirring in a water bath or oil bath at 35-60°C.
[0041] In some embodiments of the present invention, in step (2), the polymerizable monomer is added into the first mixed solution in at least two batches for mixing and stirring.
[0042] In some embodiments of the present invention, the mass of the polymerization monomer added in each batch is the same.
[0043] In some embodiments of the present invention, in step (2), the stirring speed is 400-1000 rpm, and the stirring time is 5-15 min.
[0044] In some embodiments of the present invention, in step (3), the stirring speed is 200-600 rpm, and the stirring time is 50-70 min.
[0045] In some embodiments of the present invention, in step (4), a supporting substrate is placed on the release film.
[0046] In some embodiments of the present invention, the method further comprises:
[0047] (5) mixing water, a humectant, a cross-linking agent, a photoinitiator and a water-soluble chloride salt, and stirring to form a seventh mixed solution;
[0048] (6) mixing the polymerizable monomer with the seventh mixed solution and stirring to form an eighth mixed solution;
[0049] (7) mixing the acrylic acid ester monomer with the eighth mixed solution and stirring to form a ninth mixed solution;
[0050] (8) using the low water loss hydrogel formed in step (4) as a first layer of colloid, transferring the ninth mixed solution onto the first layer of colloid, and performing UV curing to form a second layer of colloid on the first layer of colloid, thereby obtaining a low water loss hydrogel with a two-layer structure;
[0051] The weight ratio of the crosslinking agent in the first layer of colloid to the crosslinking agent in the second layer of colloid is (2.5-1.5): 1. Thus, in the prepared two-layer low water loss hydrogel, the content of the crosslinking agent in the second layer of colloid on the side of the electrode of the massage device is lower, so that the adhesion of the second layer of colloid is stronger, which is conducive to adhesion to the electrode of the massage device, while avoiding the situation that the adhesion of the first layer of colloid in contact with the skin is too strong, which is easy to adhere to the skin and difficult to detach from the skin.
[0052] In some embodiments of the present invention, step (5) comprises the following steps:
[0053] (5-1) mixing the water and the moisturizing agent and stirring to form a tenth mixed solution;
[0054] (5-2) mixing the cross-linking agent with the tenth mixed solution and stirring to form an eleventh mixed solution;
[0055] (5-3) mixing the photoinitiator with the eleventh mixed solution and stirring to form a twelfth mixed solution;
[0056] (5-4) Mixing the water-soluble chloride salt with the twelfth mixed solution and stirring to obtain a seventh mixed solution.
[0057] In some embodiments of the present invention, in step (5-1), the stirring speed is 100-500 rpm, and the stirring time is 5-10 min.
[0058] In some embodiments of the present invention, in steps (5-2), (5-3) and (5-4), the stirring speed is independently 200-600 rpm, and the stirring time is independently 5-10 min.
[0059] In some embodiments of the present invention, step (5) is performed by heating and stirring in a water bath or oil bath at 35-60°C.
[0060] In some embodiments of the present invention, in step (6), the polymerizable monomer is added into the seventh mixed liquid in at least two batches for mixing and stirring.
[0061] In some embodiments of the present invention, the mass of the polymerization monomer added in each batch is the same.
[0062] In some embodiments of the present invention, in step (6), the stirring speed is 400-1000 rpm, and the stirring time is 5-15 min.
[0063] In some embodiments of the present invention, in step (7), the stirring speed is 200-600 rpm, and the stirring time is 50-70 min.
[0064] In a third aspect of the present invention, the present invention provides a massage device. According to an embodiment of the present invention, the massage device has the low water loss hydrogel described above or the low water loss hydrogel obtained by the method described above. As a result, the massage device has a hydrogel with a water loss rate of less than 9%, thereby greatly improving the life cycle of the product.
[0065] In addition, the massage device according to the above embodiment of the present invention may also have the following additional technical features:
[0066] In some embodiments of the present invention, the massage device includes a massage device body and the low-water-loss hydrogel, the low-water-loss hydrogel includes a stacked first layer of colloid and a second layer of colloid, the second layer of colloid is used to adhere to one side of the electrode of the massage device; the weight ratio of the cross-linking agent in the first layer of colloid to the cross-linking agent in the second layer of colloid is (2.5-1.5):1.
[0067] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0069] Figure 1 The present invention is a schematic flow chart of a method for preparing a low water loss hydrogel according to an embodiment of the present invention.
[0070] Figure 2 The present invention is a schematic flow chart of a method for preparing a low water loss hydrogel according to another embodiment of the present invention.
[0071] Figure 3 The present invention is a schematic flow chart of a method for preparing a low water loss hydrogel according to another embodiment of the present invention.
[0072] Figure 4 The present invention is a schematic flow chart of a method for preparing a low water loss hydrogel according to another embodiment of the present invention. DETAILED DESCRIPTION
[0073] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0074] In one aspect of the present invention, the present invention proposes a low water loss hydrogel. According to an embodiment of the present invention, the low water loss hydrogel comprises: water, a humectant, a cross-linking agent, a photoinitiator, a water-soluble chloride salt, a polymerized monomer and an acrylate monomer; the weight ratio of the water to the humectant is (0.4-0.6):1. Thus, by limiting the weight ratio of water to the humectant in the hydrogel to within the range of (0.4-0.6):1, the water loss rate of the hydrogel is greatly reduced, and the water loss rate of the hydrogel is less than 9%, thereby improving the water holding capacity of the hydrogel, thereby greatly improving the life cycle of the hydrogel product. The inventors found that if the proportion of the humectant is too low, the hydrogel will lose water too quickly and have poor water retention; if the proportion of the humectant is too high, the conductive properties of the hydrogel will deteriorate, and the humectant will precipitate, thereby affecting the product experience.
[0075] In the embodiment of the present invention, the principle of forming a low water loss hydrogel is as follows: under the action of a photoinitiator, polymerized monomers and acrylate monomers are polymerized to form a polymer gel, which is mutually combined and entangled under the action of a cross-linking agent to form a three-dimensional network structure, i.e., a hydrogel. Chloride salt is soluble in water and acts as a conductive substance in the system. The role of the humectant is to retain water and prevent water loss in the hydrogel.
[0076] According to a specific embodiment of the present invention, the low water loss hydrogel comprises: 2-4.5 parts by weight of water, 3.1-7.5 parts by weight of a moisturizer, 0.001-0.14 parts by weight of a cross-linking agent, 0.001-0.12 parts by weight of a photoinitiator, 0.02-0.3 parts by weight of a water-soluble chloride salt, 1-5 parts by weight of a polymerizable monomer, and 0.1-2 parts by weight of an acrylate monomer. Thus, the water loss rate of the low water loss hydrogel is further reduced, thereby further improving the life cycle of the product. The inventors found that if the content of the moisturizer is too low, the hydrogel will lose water too quickly and have poor water retention. If the content of the moisturizer is too high, the conductivity of the hydrogel will deteriorate and the moisturizer will precipitate, thereby affecting the product experience. If the water content is too little, the conductivity of the hydrogel will be poor. If the water content is too much, the water will be easily lost from the hydrogel. If the content of the polymerized monomer is too low, the strength of the formed hydrogel will be too weak. If the content is too high, the strength of the hydrogel will be too high, thereby affecting the touch of the hydrogel with human skin. If the content of the acrylate monomer is too low, the The strength of the hydrogel is too weak. If its content is too high, the strength of the hydrogel will be too high, thus affecting the touch of the hydrogel with human skin; if the content of the photoinitiator is too low, the polymerization monomer and the acrylate monomer will be incompletely polymerized. If its content is too high, it will cause over-polymerization; if the content of the cross-linking agent is too low, the polymer gel will be incompletely cross-linked, thereby reducing the strength of the hydrogel. If its content is too high, it will cause over-cross-linking, resulting in the hydrogel being too strong and fragile; if the content of the conductive agent is too low, the conductivity of the hydrogel will be poor. If its content is too high, it will affect cost waste.
[0077] In the embodiments of the present invention, the specific type of the water is not particularly limited, and those skilled in the art can select it at will according to actual conditions. As a preferred solution, the water is selected from at least one of ultrapure water, distilled water and deionized water. Thus, the purity of the water is higher, and the impurities contained in the water are prevented from adversely affecting subsequent reactions, so that the comprehensive performance of the hydrogel formed is better.
[0078] In the embodiments of the present invention, the specific types of the above-mentioned moisturizing agents are not particularly limited, and those skilled in the art can freely select them according to actual conditions. As a preferred solution, the moisturizing agent is selected from at least one of glycerol, methyl propanediol, 1,3-propylene glycol and 1,2-hexanediol, thereby, the above-mentioned moisturizing agent has better water retention, and the water loss rate of the low water loss hydrogel formed thereby is further reduced, thereby further improving the life cycle of the product. More preferably, the moisturizing agent is glycerol, and there are three hydroxyl groups in the glycerol molecule. Hydrogen bonds are easily generated between hydroxyl groups and water molecules, so it has water absorption, and water itself is easy to volatilize. The intervention of glycerol can reduce the emission of water molecules.
[0079] In the embodiments of the present invention, the specific type of the above-mentioned cross-linking agent is not particularly limited, and those skilled in the art can choose it at will according to actual conditions. As a preferred scheme, the cross-linking agent is selected from at least one of aliphatic amine cross-linking agents, aromatic amine cross-linking agents, polyamide cross-linking agents and polyether amine cross-linking agents. Therefore, the above-mentioned cross-linking agent is cheap and easy to obtain, the cross-linking effect is better, and the comprehensive performance of the hydrogel formed thereby is better.
[0080] In the embodiments of the present invention, the specific type of the above-mentioned aliphatic amine cross-linking agent is not particularly limited, and those skilled in the art can choose it at will according to actual conditions. As a preferred scheme, the aliphatic amine cross-linking agent is selected from at least one of MBA, diethylenetriamine (DETA), 1,2, diaminocyclohexane (DACH) and methylenebiscyclohexaneamine (4,4'-PACM). Therefore, the above-mentioned cross-linking agent is cheap and easy to obtain, and the cross-linking effect is better, and the comprehensive performance of the hydrogel formed thereby is better.
[0081] In the embodiment of the present invention, the specific model of the above-mentioned photoinitiator is not particularly limited, and the person skilled in the art can select it at will according to the actual situation. As a preferred scheme, the model of the photoinitiator is selected from at least one of 2959 (Chinese name is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone), 1173 (Chinese name is 2-hydroxy-2-methyl-1-phenyl-1-propanone), 907 (Chinese name is 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone) and 184 (Chinese name is 1-hydroxycyclohexylphenyl ketone). Therefore, the above-mentioned photoinitiator is cheap and easy to obtain, and the photoinitiation effect is better, and the comprehensive performance of the hydrogel formed thereby is better. 2959 is more preferred, because the absorption wavelength of the photoinitiator 2959 is in the range of 200-370 nanometers, which meets the irradiation requirements of the ultraviolet lamp in the subsequent curing step. At the same time, 2959 has a small odor, high efficiency and no yellowing, and is particularly suitable for water-based system formulation materials.
[0082] In the embodiments of the present invention, the specific type of the water-soluble chloride salt is not particularly limited, and those skilled in the art can select it at will according to the actual situation. As a preferred solution, the water-soluble chloride salt is selected from at least one of anhydrous lithium chloride, sodium chloride and ammonium chloride, so that the chloride salt is 100% hydrolyzed, and its conductivity is better, and the conductivity of the hydrogel formed thereby is better. Anhydrous lithium chloride is more preferred, because sodium chloride will reduce the solubility of sodium acrylate monomer in the aqueous system, while anhydrous lithium chloride does not have this disadvantage, that is, by using anhydrous lithium chloride, the uniformity of the aqueous system of the hydrogel is better.
[0083] In the embodiments of the present invention, the specific types of the above-mentioned polymerizable monomers are not particularly limited, and those skilled in the art can select them at will according to actual conditions. As a preferred scheme, the polymerizable monomers are selected from at least one of acrylamide monomers, acrylic acid monomers, sodium acrylate monomers and chitosan monomers. Therefore, the polymerization effect of the above-mentioned polymerizable monomers is better, and the comprehensive performance of the hydrogel formed thereby is better. In addition, the above-mentioned polymerizable monomers have low skin sensitization, especially the sodium acrylate monomer has almost no skin sensitization.
[0084] In the embodiments of the present invention, the specific types of the above-mentioned acrylic acid ester monomers are not particularly limited, and those skilled in the art can freely select them according to actual conditions. As a preferred scheme, the acrylic acid ester monomers are selected from at least one of hydroxyethyl methacrylate and hydroxypropyl methacrylate. Therefore, the polymerization effect of the above-mentioned acrylic acid ester monomers is better, and the viscosity of the hydrogel formed thereby is better.
[0085] According to another specific embodiment of the present invention, the low water loss hydrogel further includes a fragrance additive, thereby making the hydrogel have a pleasant smell, further improving the user experience. In the embodiment of the present invention, the amount of the fragrance additive added is not particularly limited, as long as it can make the hydrogel have a pleasant smell, and generally the amount added is one drop.
[0086] In the embodiments of the present invention, the specific types of the above-mentioned flavor additives are not particularly limited, and those skilled in the art can select them at will according to actual conditions. As a preferred solution, the flavor additives are selected from at least one of essences and essential oils, thereby further making the low water loss hydrogel have a pleasant smell, further improving the user experience.
[0087] According to another specific embodiment of the present invention, the low water loss hydrogel further includes a cooling agent, thereby making the hydrogel feel cool and further improving the user experience. In the embodiment of the present invention, the amount of the cooling agent added is not particularly limited, as long as it can make the hydrogel feel cool, and generally the amount added is one drop.
[0088] In the embodiments of the present invention, the specific type of the above-mentioned cooling agent is not particularly limited, and those skilled in the art can choose it at will according to the actual situation. As a preferred scheme, the cooling agent is selected from at least one of mint essence, menthol and menthol, thereby further making the low water loss hydrogel have a pleasant smell, further improving the user experience.
[0089] According to another specific embodiment of the present invention, the low water loss hydrogel further includes 0.0015 parts by weight of a skin conditioner, thereby enabling the hydrogel to have a skin conditioning function, further improving the user experience.
[0090] In the embodiments of the present invention, the specific type of the skin conditioner is not particularly limited, and those skilled in the art can select it at will according to actual conditions. As a preferred embodiment, the skin conditioner is selected from at least one of rose water and parahydroxyacetophenone, thereby further enabling the hydrogel to have the function of conditioning the skin, further improving the user experience.
[0091] According to another specific embodiment of the present invention, the low water loss hydrogel includes a first layer of colloid and a second layer of colloid, and the second layer of colloid is used to adhere to one side of the electrode of the massage device; the weight ratio of the crosslinker in the first layer of colloid to the crosslinker in the second layer of colloid is (2.5-1.5):1. Therefore, by setting a two-layer structure, the content of the crosslinker in the second layer of colloid that adheres to one side of the electrode of the massage device is lower, so that the adhesion of the second layer of colloid is stronger, which is conducive to adhesion to the electrode of the massage device, and at the same time avoids the situation that the adhesion of the first layer of colloid in contact with the skin is too strong, which is easy to adhere to the skin and difficult to detach from the skin. The inventor found that the lower the content of the crosslinker, the less the number of crosslinks with the polymer, the smaller the crosslinking density, and the material is soft in macroscopic performance and relatively high in viscosity; conversely, the larger the amount of crosslinker used, the greater the crosslinking density, the harder the material is in macroscopic performance and the lower the viscosity. The viscosity of the second layer of colloid is within the range of 200-500g / 25mm, and it is used to bond the metal electrodes of the massage device. This viscosity can have good bonding properties with the metal. After being placed at a high temperature of 45°C for 8 hours, the colloid gel will not remain on the metal surface when it is removed; the viscosity of the first layer of colloid is within the range of 50-300g / 25mm, and it is used for contact with human skin.
[0092] According to another specific embodiment of the present invention, the thickness of the first colloid layer is 0.6-0.8 mm, and the thickness of the second colloid layer is 0.2-0.4 mm. The inventors found that if the thickness of the first colloid layer is too small, the adhesion of the first colloid layer will be too small; if the thickness of the first colloid layer is too large, the conductive property of the first colloid layer will be affected; if the thickness of the second colloid layer is too small, the adhesion of the second colloid layer will be too small; if the thickness of the second colloid layer is too large, the conductive property of the second colloid layer will be affected.
[0093] In yet another aspect of the present invention, the present invention provides a method for preparing the above-mentioned low water loss hydrogel. Figure 1 , the method comprising:
[0094] S100: Mix water, humectant, crosslinker, photoinitiator and water-soluble chloride salt and stir.
[0095] In this step, water, a humectant, a crosslinking agent, a photoinitiator and a water-soluble chloride salt are mixed and stirred to form a first mixed solution. The mixing method and stirring method of the water, humectant, crosslinking agent, photoinitiator and water-soluble chloride salt are not particularly limited, as long as the above substances can be mixed evenly.
[0096] According to another specific embodiment of the present invention, refer to the attached Figure 2 , the above step S100 further includes the following steps:
[0097] S110: mixing the water and the moisturizing agent and stirring to form a fourth mixed solution;
[0098] S120: mixing the cross-linking agent with the fourth mixed solution and stirring to form a fifth mixed solution;
[0099] S130: mixing the photoinitiator with the fifth mixed liquid and stirring to form a sixth mixed liquid;
[0100] S140: Mixing the water-soluble chloride salt with the sixth mixed solution and stirring to obtain a first mixed solution.
[0101] The inventors found that water is easy to volatilize, and adding a moisturizer to the mixture can effectively reduce the volatilization of water. Therefore, the water and the moisturizer are first mixed to form a fourth mixed liquid; and the solubility of the cross-linking agent and the photoinitiator is lower than that of the water-soluble chloride salt. Therefore, the cross-linking agent and the photoinitiator are first added to the mixed liquid and stirred for a period of time, and then the water-soluble chloride salt is finally added to the mixed liquid, thereby forming a first mixed liquid with better uniformity.
[0102] According to another specific embodiment of the present invention, in step S110, the stirring speed is 100-500 rpm, and the stirring time is 5-10 min, so that the uniformity of the fourth mixed liquid is better. The inventors found that since the moisturizer is an amphoteric substance, if the speed is too fast, a large number of bubbles (such as soap) are easily generated; if the speed is too slow, it will cause uneven dispersion, and the uniformity of the fourth mixed liquid is not good.
[0103] According to another specific embodiment of the present invention, in steps S120, S130 and S140, the stirring rotation speed is independently 200-600 rpm, and the stirring time is independently 5-10 min, thereby, the fifth mixed liquid, the sixth mixed liquid and the first mixed liquid have better uniformity.
[0104] According to another specific embodiment of the present invention, step S100 is heated and stirred in a water bath or oil bath at 35-60°C, preferably an oil bath. The advantage of an oil bath is that the temperature is more evenly controlled. Therefore, within this temperature range, the first mixed liquid formed by the above-mentioned substances has better uniformity.
[0105] S200: Mix the polymerization monomer with the first mixed solution and stir
[0106] In this step, the polymerizable monomer is mixed with the first mixed solution and stirred to form a second mixed solution. The mixing method and stirring method of the above-mentioned polymerizable monomer and the first mixed solution are not particularly limited, as long as the above-mentioned substances can be mixed evenly. Since the polymerizable monomer is easily oxidized, it cannot be heated in this step. The inventors have found that since the viscosity of the polymerizable monomer is greater than that of the crosslinking agent and the photoinitiator, it is necessary to form a mixed solution of the crosslinking agent and the photoinitiator before adding the polymerizable monomer. If the polymerizable monomer is dissolved first and then the crosslinking agent and the photoinitiator are added, the viscosity of the polymerizable monomer mixed solution is too high, and the crosslinking agent and the photoinitiator cannot be evenly dispersed in the polymerizable monomer mixed solution.
[0107] According to another specific embodiment of the present invention, the polymerization monomer is added into the first mixed liquid in at least two batches for mixing and stirring. The inventors have found that if the polymerization monomer is added all at once, it will cause the polymerization monomer to agglomerate and disperse unevenly. Adding it in batches is more conducive to fully dispersing the polymerization monomer in the first mixed liquid, thereby forming a second mixed liquid with better uniformity.
[0108] According to another specific embodiment of the present invention, the mass of the polymerizable monomers added in each batch is the same, which is more conducive to fully dispersing the polymerizable monomers in the first mixed liquid, and the uniformity of the formed second mixed liquid is better.
[0109] According to another specific embodiment of the present invention, in step S200, the stirring speed is 400-1000 rpm, and the stirring time is 5-15 min, thereby, the second mixed liquid formed has better uniformity.
[0110] S300: Mix the acrylic acid ester monomer and the second mixed liquid, and stir
[0111] In this step, the acrylic ester monomer is mixed with the second mixed liquid and stirred to form a third mixed liquid. The mixing method and stirring method of the acrylic ester monomer and the second mixed liquid are not particularly limited, as long as the above substances can be mixed evenly. The inventors have found that since the viscosity of the acrylic ester monomer is greater than that of the polymerizable monomer, it is necessary to first form a mixed liquid of the polymerizable monomer and then add the acrylic ester monomer. If the acrylic ester monomer is dissolved first and then the polymerizable monomer is added, the viscosity of the acrylic ester monomer mixed liquid is too high, and the polymerizable monomer cannot be evenly dispersed in the acrylic ester monomer mixed liquid.
[0112] According to another specific embodiment of the present invention, in step S300, the stirring speed is 200-600 rpm, and the stirring time is 50-70 min, thereby the third mixed liquid has better uniformity.
[0113] S400: Transfer the third mixed solution to the release film and perform UV curing
[0114] In this step, the third mixed solution is transferred to a release film and UV cured to obtain a low water loss hydrogel. The specific process of UV curing belongs to the conventional technology in this field and will not be described here.
[0115] According to another specific embodiment of the present invention, in step S400, a supporting substrate is placed on the release film, and the supporting substrate serves as a skeleton to enhance the strength of the hydrogel system. The specific type of the supporting substrate is not particularly limited, as long as it can play a supporting role, such as supporting non-woven fabric.
[0116] According to another specific embodiment of the present invention, refer to the attached Figure 3 The above method also includes S500-S800, thereby preparing a two-layer structure of low water loss hydrogel, the second layer of colloid on the side of the electrode of the massage device is adhered to a lower content of cross-linking agent, so that the second layer of colloid has stronger adhesion, which is conducive to adhesion to the electrode of the massage device, while avoiding the situation that the first layer of colloid in contact with the skin has too strong adhesion, which is easy to adhere to the skin and difficult to detach from the skin.
[0117] The following describes steps S500-S800 in detail:
[0118] S500: Mix water, humectant, crosslinker, photoinitiator and water-soluble chloride salt and stir.
[0119] In this step, water, a humectant, a crosslinking agent, a photoinitiator and a water-soluble chloride salt are mixed and stirred to form a seventh mixed solution. The mixing method and stirring method of the water, humectant, crosslinking agent, photoinitiator and water-soluble chloride salt are not particularly limited, as long as the above substances can be mixed evenly.
[0120] According to another specific embodiment of the present invention, refer to the attached Figure 4 , the above step S500 further includes the following steps:
[0121] S510: mixing the water and the moisturizing agent and stirring to form a tenth mixed solution;
[0122] S520: mixing the cross-linking agent with the tenth mixed solution and stirring to form an eleventh mixed solution;
[0123] S530: mixing the photoinitiator with the eleventh mixed solution, and stirring to form a twelfth mixed solution;
[0124] S540: Mix the water-soluble chloride salt with the twelfth mixed solution, and stir to obtain a seventh mixed solution.
[0125] The inventors found that water is easy to volatilize, and adding a moisturizer to the mixture can effectively reduce the volatilization of water. Therefore, the water and the moisturizer are first mixed to form a tenth mixed liquid; and the solubility of the cross-linking agent and the photoinitiator is lower than that of the water-soluble chloride salt. Therefore, the cross-linking agent and the photoinitiator are first added to the mixed liquid and stirred for a period of time, and then the water-soluble chloride salt is finally added to the mixed liquid. Thus, the uniformity of the formed seventh mixed liquid is better.
[0126] According to another specific embodiment of the present invention, in step S510, the stirring speed is 100-500 rpm, and the stirring time is 5-10 min, so that the uniformity of the tenth mixed solution is better. The inventors found that since the moisturizer is an amphoteric substance, if the speed is too fast, a large number of bubbles (such as soap) are easily generated; if the speed is too slow, it will lead to uneven dispersion, and the uniformity of the tenth mixed solution is not good.
[0127] According to another specific embodiment of the present invention, in steps S520, S530 and S540, the stirring rotation speed is independently 200-600 rpm, and the stirring time is independently 5-10 min, thereby, the eleventh mixed liquid, the twelfth mixed liquid and the seventh mixed liquid have better uniformity.
[0128] According to another specific embodiment of the present invention, step S500 is heated and stirred in a water bath or oil bath at 35-60°C, preferably an oil bath. The advantage of an oil bath is that the temperature is more evenly controlled. Therefore, within this temperature range, the uniformity of the seventh mixed liquid formed by the above-mentioned substances is better.
[0129] S600: Mix the polymerization monomer with the seventh mixed solution and stir
[0130] In this step, the polymerizable monomer is mixed with the seventh mixed solution and stirred to form an eighth mixed solution. The mixing method and stirring method of the above-mentioned polymerizable monomer and the seventh mixed solution are not particularly limited, as long as the above-mentioned substances can be mixed evenly. Since the polymerizable monomer is easily oxidized, it cannot be heated in this step. The inventors found that since the viscosity of the polymerizable monomer is greater than that of the crosslinking agent and the photoinitiator, it is necessary to form a mixed solution of the crosslinking agent and the photoinitiator before adding the polymerizable monomer. If the polymerizable monomer is dissolved first and then the crosslinking agent and the photoinitiator are added, the viscosity of the polymerizable monomer mixed solution is too high, and the crosslinking agent and the photoinitiator cannot be evenly dispersed in the polymerizable monomer mixed solution.
[0131] According to another specific embodiment of the present invention, the polymerization monomer is added into the seventh mixed liquid in at least two batches for mixing and stirring. The inventors have found that if the polymerization monomer is added all at once, it will cause the polymerization monomer to agglomerate and disperse unevenly. Adding it in batches is more conducive to fully dispersing the polymerization monomer in the seventh mixed liquid. As a result, the formed eighth mixed liquid has better uniformity.
[0132] According to another specific embodiment of the present invention, the mass of the polymerization monomers added in each batch is the same, which is more conducive to fully dispersing the polymerization monomers in the seventh mixed liquid, and the uniformity of the formed eighth mixed liquid is better.
[0133] According to another specific embodiment of the present invention, in step S600, the stirring speed is 400-1000 rpm, and the stirring time is 5-15 min, thereby, the uniformity of the formed eighth mixed liquid is better.
[0134] S700: Mix the acrylic acid ester monomer with the eighth mixed solution and stir
[0135] In this step, the acrylic ester monomer is mixed with the eighth mixed solution and stirred to form a ninth mixed solution. The mixing method and stirring method of the acrylic ester monomer and the eighth mixed solution are not particularly limited, as long as the above substances can be mixed evenly. The inventors found that since the viscosity of the acrylic ester monomer is greater than that of the polymerizable monomer, it is necessary to first form a mixed solution of the polymerizable monomer and then add the acrylic ester monomer. If the acrylic ester monomer is dissolved first and then the polymerizable monomer is added, the viscosity of the acrylic ester monomer mixed solution is too high, and the polymerizable monomer cannot be evenly dispersed in the acrylic ester monomer mixed solution.
[0136] According to another specific embodiment of the present invention, in step S700, the stirring speed is 200-600 rpm, and the stirring time is 50-70 min, thereby, the uniformity of the ninth mixed liquid formed is better.
[0137] S800: Using the low water loss hydrogel formed in step S400 as the first layer of colloid, transferring the ninth mixed solution onto the first layer of colloid, and performing UV curing
[0138] In this step, the low water loss hydrogel formed in step S400 is used as the first layer of colloid, the ninth mixed solution is transferred to the first layer of colloid, and UV curing is performed to form a second layer of colloid on the first layer of colloid to obtain a low water loss hydrogel with a two-layer structure. The specific process of UV curing belongs to the conventional technology in the field and will not be repeated here.
[0139] According to the method of using the low water loss hydrogel in the embodiment of the present invention, the water loss rate of the hydrogel is greatly reduced by limiting the weight ratio of water and moisturizing agent in the hydrogel to the range of (0.4-0.6):1, and the water loss rate of the hydrogel is less than 9%, thereby improving the water holding capacity of the hydrogel, thereby greatly improving the life cycle of the hydrogel product. The inventors found that if the proportion of moisturizing agent is too low, the hydrogel will lose water too quickly and have poor water retention capacity; if the proportion of moisturizing agent is too high, the conductive properties of the hydrogel will deteriorate, and the moisturizing agent will precipitate.
[0140] In a third aspect of the present invention, the present invention provides a massage device. According to an embodiment of the present invention, the massage device has the low water loss hydrogel described above or the low water loss hydrogel obtained by the method described above. As a result, the massage device has a hydrogel with a water loss rate of less than 9%, thereby greatly improving the life cycle of the product.
[0141] According to another specific embodiment of the present invention, the massage device includes a massage device body and the low water-loss hydrogel, the low water-loss hydrogel includes a stacked first layer of colloid and a second layer of colloid, the second layer of colloid is used to adhere to one side of the electrode of the massage device; the weight ratio of the cross-linking agent in the first layer of colloid to the cross-linking agent in the second layer of colloid is (2.5-1.5):1, thereby, the content of the cross-linking agent in the second layer of colloid adhering to one side of the electrode of the massage device is lower, so that the adhesion of the second layer of colloid is stronger, which is conducive to adhesion to the electrode of the massage device, while avoiding the situation that the adhesion of the first layer of colloid in contact with the skin is too strong, which is easy to adhere to the skin and difficult to detach from the skin.
[0142] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0143] Example 1
[0144] This embodiment provides a low water loss hydrogel and a preparation method thereof. The low water loss hydrogel comprises a first layer of colloid and a second layer of colloid. The formula of the first layer of colloid is shown in Table 1, and the formula of the second layer of colloid is shown in Table 2.
[0145] Table 1 Formula of the first layer of colloid
[0146] Case Components Example 1 Example 2 Example 3 Example 4 Sodium acrylate(g) 3 3 3 3 Hydroxyethyl methacrylate(g) 0.145 0.145 0.145 0.69 Crosslinking agent MBA(g) 0.108 0.108 0.108 0.127 Photoinitiator 2959(g) 0.0079 0.0079 0.0079 0.0916 Pure water(g) 3 3.5 4 3 Glycerin(g) 7 6.5 6.7 7 Anhydrous lithium chloride (g) 0.024 0.024 0.024 0.024 peppermint 1 drop 1 drop 1 drop 1 drop
[0147] Table 2 Formula of the second layer of colloid
[0148] Case Components Example 1 Example 2 Example 3 Example 4 Sodium acrylate(g) 3 3 3 3 Hydroxyethyl methacrylate(g) 0.145 0.145 0.145 0.69 Crosslinking agent MBA(g) 0.0054 0.0054 0.0054 0.0638 Photoinitiator 2959(g) 0.0079 0.0079 0.0079 0.0916 Pure water(g) 3 3.5 4 3 Glycerin(g) 7 6.5 6.7 7 Anhydrous lithium chloride (g) 0.024 0.024 0.024 0.024 peppermint 1 drop 1 drop 1 drop 1 drop
[0149] Preparation of the first colloid layer:
[0150] (a) According to the content of each substance in Table 1, ultrapure water was weighed and added to glycerol, and heated and stirred in a water bath at 50°C, and stirred at a speed of 200 rpm for 8 min to mix evenly;
[0151] (b) adding crosslinking agent MBA and mixing at 500 rpm for 8 min until mixed evenly;
[0152] (c) adding photoinitiator (2959) and mixing at 500 rpm for 8 min until the mixture is uniformly mixed;
[0153] (d) adding anhydrous lithium chloride and mixing at 500 rpm for 8 min until the mixture is uniformly mixed;
[0154] (e) Stop heating, weigh sodium acrylate powder (easy to oxidize, so stop heating), add it to the solution in batches, and mix at 700 rpm. At first, the solution is off-white. After about 10 minutes, the solution begins to become clear and transparent. After it becomes transparent, add hydroxyethyl methacrylate (to provide viscosity) and stir at 500 rpm for 1 hour to become a light yellow or transparent solution (water quality affects the color, and transparency means less impurities);
[0155] (f) The mixed solution prepared in the above step is scraped onto the release film, wherein a supporting non-woven fabric is placed on the release film, and subjected to the first UV curing (irradiation time 3s and power 4KW) to form a first layer of colloid with a thickness of 0.7mm.
[0156] Preparation of the second colloid layer:
[0157] (g) Prepare and mix according to the contents of the substances in Table 2;
[0158] (h) The mixed solution prepared in step (g) is scraped onto the first layer of colloid, and a second UV curing is performed (irradiation time is 3 s and power is 4 kW) to form a second layer of colloid on the first layer of colloid. The thickness of the second layer of colloid is 0.3 mm, thereby obtaining a two-layer structure of low water loss hydrogel.
[0159] Example 2
[0160] This embodiment provides a low water loss hydrogel and a preparation method thereof. The low water loss hydrogel comprises a first layer of colloid and a second layer of colloid. The formula of the first layer of colloid is shown in Table 1, and the formula of the second layer of colloid is shown in Table 2.
[0161] The preparation method is the same as that of Example 1.
[0162] Example 3
[0163] This embodiment provides a low water loss hydrogel and a preparation method thereof. The low water loss hydrogel comprises a first layer of colloid and a second layer of colloid. The formula of the first layer of colloid is shown in Table 1, and the formula of the second layer of colloid is shown in Table 2.
[0164] The preparation method is the same as that of Example 1.
[0165] Example 4
[0166] This embodiment provides a low water loss hydrogel and a preparation method thereof. The low water loss hydrogel comprises a first layer of colloid and a second layer of colloid. The formula of the first layer of colloid is shown in Table 1, and the formula of the second layer of colloid is shown in Table 2.
[0167] The preparation method is the same as that of Example 1.
[0168] Comparative Example 1
[0169] The content of pure water in this comparative example is 2 g, the content of glycerol is 8 g, and the other contents are the same as those in Example 1.
[0170] Comparative Example 2
[0171] The content of pure water in this comparative example is 5 g, the content of glycerol is 5 g, and the other contents are the same as those in Example 4.
[0172] After the low water loss hydrogel prepared in Examples 1-4 and the hydrogel prepared in Comparative Examples 1-2 were placed at room temperature for 24 hours, the adhesion (peel force), conductivity, water loss rate and material tensile strength were evaluated and tested. The test results are shown in Table 3.
[0173] The present invention adopts high temperature baking method to test the water loss rate:
[0174] First weigh the original weight of the gel G1;
[0175] Bake at 45℃ (high temperature drying oven) for 8 hours, take out, and weigh the weight after baking G2;
[0176] Final water loss rate = (G1-G2) / G1.
[0177] Table 3
[0178] Case performance Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Tensile Strength good good good generally generally Difference Second layer colloid peeling force 389g 469g 389g 298g 524g 472g First layer colloid peeling force 260g 235g 200g 137g 316g 278g AC impedance 400Ω 550Ω 650Ω 890Ω 1067Ω 1227Ω Experience Strength obvious obvious obvious obvious Not obvious Not obvious Original weight / g 1.6212 1.4105 1.4774 1.588 0.6911 0.7572 Weight after baking / g 1.4953 1.292 1.3576 1.4642 0.57 0.6326 Weight loss / g 0.1259 0.1185 0.1198 0.1238 0.1211 0.1246 Water loss rate / % 7.77% 8.40% 8.11% 7.80% 17.52% 16.46%
[0179] As can be seen from Table 3, the water loss rate of the low water loss hydrogel prepared in Examples 1-4 is less than 9%, while the water loss rate of the hydrogel in Comparative Example 1-2 is above 16%, which is a relatively high water loss rate. It can be seen that the water loss rate of the low water loss hydrogel prepared in Examples 1-4 is significantly lower than that in Comparative Example 1-2, which indicates that when the weight ratio of water to moisturizer is in the range of (0.4-0.6):1, the water holding effect of the hydrogel is particularly good. If it is higher or lower than this range, the water holding effect of the hydrogel is poor. It can also be seen from Table 3 that in the two-layer low water loss hydrogel prepared in Examples 1-4, the peeling force of the second layer of colloid on the side of the electrode of the massage device is significantly greater than the peeling force of the first layer of colloid in contact with the skin, making the second layer of colloid more conducive to adhesion to the electrode of the massage device, while avoiding the situation that the adhesion of the first layer of colloid in contact with the skin is too strong, which is easy to adhere to the skin and difficult to detach from the skin.
[0180] In addition, it can be seen from Table 3 that the low water loss hydrogels prepared in Examples 1-4 have suitable tensile strength, are soft and tough, and are not easy to tear apart; while the materials in Comparative Examples 1-2 are very soft, have low toughness, poor tensile strength, and poor processing performance. AC impedance is the result of measuring the gel sheet at a frequency of 1 kilohertz with two gel sheets of the same size clamped together. The AC impedances of the low water loss hydrogels prepared in Examples 1-4 are all less than 1000 ohms, and the current stimulation obviously has a strong experience intensity; while the AC impedances of Comparative Examples 1-2 are all higher than 1000Ω, and the experience intensity tends to decrease, accompanied by a certain tingling sensation.
[0181] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0182] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A low water loss hydrogel, characterized in that: include: Water, humectant, cross-linking agent, photoinitiator, water-soluble chloride salt, polymerization monomer and acrylate monomer; The polymerizable monomer is selected from at least one of acrylamide monomer, acrylic acid monomer and sodium acrylate monomer; The weight ratio of the water to the moisturizing agent is (0.4-0.6):1; The invention comprises: 2-4.5 parts by weight of water, 3.1-7.5 parts by weight of a moisturizer, 0.001-0.14 parts by weight of a crosslinking agent, 0.001-0.12 parts by weight of a photoinitiator, 0.02-0.3 parts by weight of a water-soluble chloride salt, 1-5 parts by weight of a polymerizable monomer, and 0.1-2 parts by weight of an acrylate monomer. The low water loss hydrogel comprises a first layer of colloid and a second layer of colloid stacked together, wherein the second layer of colloid is used to adhere to one side of the electrode of the massage device; The weight ratio of the crosslinking agent in the first layer of colloid to the crosslinking agent in the second layer of colloid is (2.5-1.5):
1.
2. The low water loss hydrogel according to claim 1, characterized in that: The water is selected from at least one of ultrapure water, distilled water and deionized water.
3. The low water loss hydrogel according to claim 1, characterized in that The moisturizing agent is selected from at least one of glycerin, methyl propanediol, 1,3-propylene glycol and 1,2-hexanediol.
4. The low water loss hydrogel according to any one of claims 1 to 3, characterized in that The cross-linking agent is selected from MBA.
5. The low water loss hydrogel according to any one of claims 1 to 3, characterized in that: The photoinitiator has a model number selected from at least one of 2959, 1173, 907 and 184.
6. The low water loss hydrogel according to any one of claims 1 to 3, characterized in that The water-soluble chloride salt is selected from at least one of anhydrous lithium chloride, sodium chloride and ammonium chloride.
7. The low water loss hydrogel according to any one of claims 1 to 3, characterized in that The acrylic acid ester monomer is selected from at least one of hydroxyethyl methacrylate and hydroxypropyl methacrylate.
8. The low water loss hydrogel according to any one of claims 1 to 3, characterized in that: Also included are flavor additives.
9. The low water loss hydrogel according to claim 8, characterized in that: The flavor additive is selected from at least one of essence and essential oil.
10. The low water loss hydrogel according to any one of claims 1 to 3, characterized in that: Also includes cooling agents.
11. The low water loss hydrogel according to claim 10, characterized in that: The cooling agent is selected from at least one of mint essence, menthol and menthol.
12. The low water loss hydrogel according to any one of claims 1 to 3, characterized in that: Also included is 0.0015 parts by weight of a skin conditioning agent.
13. The low water loss hydrogel according to claim 12, characterized in that: The skin conditioning agent is selected from at least one of rose water and p-hydroxyacetophenone.
14. The low water loss hydrogel according to claim 1, characterized in that: The thickness of the first colloid layer is 0.6-0.8 mm, and the thickness of the second colloid layer is 0.2-0.4 mm.
15. A method for preparing the low water loss hydrogel according to any one of claims 1 to 14, characterized in that: include: (1) mixing water, a humectant, a crosslinking agent, a photoinitiator and a water-soluble chloride salt, and stirring to form a first mixed solution; (2) mixing the polymerizable monomer with the first mixed solution and stirring to form a second mixed solution; (3) mixing the acrylic acid ester monomer with the second mixed solution and stirring to form a third mixed solution; (4) transferring the third mixed solution to a release film and performing UV curing to obtain a low water loss hydrogel; (5) mixing water, a humectant, a crosslinking agent, a photoinitiator and a water-soluble chloride salt, and stirring to form a seventh mixed solution; (6) mixing the polymerizable monomer with the seventh mixed solution and stirring to form an eighth mixed solution; (7) mixing the acrylic acid ester monomer with the eighth mixed solution and stirring to form a ninth mixed solution; (8) The low water-loss hydrogel formed in step (4) is used as a first layer of colloid, the ninth mixed solution is transferred to the first layer of colloid, and UV curing is performed to form a second layer of colloid on the first layer of colloid, thereby obtaining a two-layer structure of low water-loss hydrogel.
16. The method according to claim 15, characterized in that Step (1) comprises the following steps: (1-1) mixing the water and the moisturizing agent and stirring to form a fourth mixed solution; (1-2) mixing the cross-linking agent with the fourth mixed solution and stirring to form a fifth mixed solution; (1-3) mixing the photoinitiator with the fifth mixed solution and stirring to form a sixth mixed solution; (1-4) Mixing the water-soluble chloride salt with the sixth mixed solution and stirring to obtain a first mixed solution.
17. The method according to claim 16, characterized in that In step (1-1), the stirring speed is 100-500 rpm, and the stirring time is 5-10 min.
18. The method according to claim 16, characterized in that In steps (1-2), (1-3) and (1-4), the stirring speed is independently 200-600 rpm, and the stirring time is independently 5-10 min.
19. The method according to claim 15, characterized in that Step (1) heating and stirring in a water bath or oil bath at 35-60°C; Optionally, in step (2), the polymerizable monomer is added into the first mixed solution in at least two batches and mixed and stirred; Optionally, the mass of the polymerization monomer added in each batch is the same; Optionally, in step (2), the stirring speed is 400-1000 rpm, and the stirring time is 5-15 min; Optionally, in step (3), the stirring speed is 200-600 rpm, and the stirring time is 50-70 min; Optionally, in step (4), a supporting substrate is placed on the release film.
20. The method according to claim 15, characterized in that Step (5) comprises the following steps: (5-1) mixing the water and the moisturizing agent and stirring to form a tenth mixed solution; (5-2) mixing the cross-linking agent with the tenth mixed solution and stirring to form an eleventh mixed solution; (5-3) mixing the photoinitiator with the eleventh mixed solution and stirring to form a twelfth mixed solution; (5-4) Mixing the water-soluble chloride salt with the twelfth mixed solution and stirring to obtain a seventh mixed solution.
21. The method according to claim 20, characterized in that In step (5-1), the stirring speed is 100-500 rpm, and the stirring time is 5-10 min.
22. The method according to claim 20, characterized in that In steps (5-2), (5-3) and (5-4), the stirring speed is independently 200-600 rpm, and the stirring time is independently 5-10 min.
23. The method according to claim 15, characterized in that Step (5) heating and stirring in a water bath or oil bath at 35-60°C; Optionally, in step (6), the polymerizable monomer is added into the seventh mixed solution in at least two batches and mixed and stirred; Optionally, in step (6), the stirring speed is 400-1000 rpm, and the stirring time is 5-15 min; Optionally, in step (7), the stirring speed is 200-600 rpm, and the stirring time is 50-70 min.
24. A massage device, characterized in that: A low water loss hydrogel according to any one of claims 1 to 14 or a low water loss hydrogel prepared by the method according to any one of claims 15 to 23, The massage device includes a massage device body and the low-water-loss hydrogel, wherein the low-water-loss hydrogel includes a stacked first layer of colloid and a second layer of colloid, wherein the second layer of colloid is used to adhere to one side of an electrode of the massage device; the weight ratio of the crosslinking agent in the first layer of colloid to the crosslinking agent in the second layer of colloid is (2.5-1.5):1.
Citation Information
Patent Citations
Hydrogel
CN109715400A
Gel assembly, massage head, neck massage instrument and wearable massage equipment
CN112121295A
Electrically conductive adhesive hydrogels with solubilizer
US20050137276A1